Richard, Are We There Yet? An Internet of Nano Things Information System Architecture - Strobel, Gero; Mittnacht, Judith (Proceedings of the 54th Hawaii International Conference on System Sciences (HICSS), 2021)
Richard Feynman’s visionary lecture at Caltech, which dates back more than half a century, is regarded as the birth of today's nanotechnology. Over time, many nanotechnology-based approaches, methods, and innovations have been adopted in almost all research disciplines. This nano-centered evolution is currently transforming the traditional paradigm of the Internet of Things into the Internet of Nano Things. However, the focus here is not on the mere adaptation of down scaling and is instead primarily on the effects and characteristics that result from this new scale. To fully exploit these new possibilities and combine them with existing added-value technologies, it is not sufficient to miniaturize existing Internet-of-Things- based systems—they must be developed from scratch. Against this background, this study examines the main areas of nanotechnology in combination with the Internet of Things phenomenon and, based on an exploratory literature search, presents an information system architecture for IoNT-based information systems.
Keywords: Internet of Nano Things; Internet of Bio-Nano Things; Internet of Things; Information System Architecture